Determinación de alteraciones anatomopatológicas en pescado que se expende en el mercado municipal del cantón Baños - Montoya Mariño, Kelly Mayli (2025)
In the Baños canton market, Tungurahua province, at 1820 meters above sea level, the prevalence of pathological abnormalities in fish sold in the Baños municipal market was determined. In this context, 100 fish specimens sold were evaluated to characterize the pathological alterations. A Chi2 test was applied to analyze the data. The objectives were: 1) To identify the main macroscopic alterations present in fish sold in the Baños canton municipal market. 2) To quantify the prevalence of pathological alterations according to species. 3) To determine whether there is an association between the pathological lesions and the fish species. The results showed that 56% had shiny skin with transparent mucus. In the eyes, 44% had opaque pupils, and in the gills, 39% were found to be in good condition. The operculum was unaltered in 100% of the specimens, although 43% had ruptured fins. The anus was unaltered in 49% of the specimens, while 37% had protrusion. Among internal organs, 43% of the livers and 42% of the spleens were bright red, but 75% of the kidneys were found adherent to the spine. The swim bladder was unaltered in 84% of the specimens, the flesh was firm and elastic in 46%, and 40% had a characteristic seaweed odor. A significant association was found between the alterations and the species (p < 0.0001), concluding that deficiencies in handling and sanitary control compromise the quality and safety of the fish.